Association of TLR3 single nucleotide polymorphisms with susceptibility to HTLV-1 infection in Iranian asymptomatic blood donors - Habibabadi,Hossein Mehrabi (2020)
Abstract INTRODUCTION: The human T-lymphotropic virus type 1 (HTLV-1) has a single-stranded RNA genome and expresses specific proteins that have oncogenic potential. Approximately 15 to 20 million people worldwide have been infected by this virus. Changes in protein or gene expression are the effects of single nucleotide polymorphisms (SNPs) within the Toll-like receptor 3 (TLR3) gene. The function and efficacy of signal transduction also lead to modified immune responses. The present study aimed to investigate the association of SNPs within TLR3 (rs3775291 and rs3775296) with susceptibility to HTLV-1 infection in Iranian asymptomatic blood donors. METHODS: This study was performed on 100 HTLV-1-infected asymptomatic blood donors and 118 healthy blood donors. Genomic DNA from all participants was purified and then amplified using specific PCR primers. SNPs within TLR3 were evaluated using the restriction fragmentation length polymorphism technique, and the results were analyzed using SPSS software (version 22). RESULTS: The frequencies of the TLR3 (rs3775296) CC, CA, AA genotypes were 70%, 24%, and 6% in the patient group, and 50.8%, 44.9%, and 4.2% in the control group, respectively. There was a significant difference in the frequency distribution of TLR3 (rs3775296) genotypes and alleles, but not in the frequency distribution of TLR3 (rs3775291) genotypes between the patient and control groups. CONCLUSIONS: The TLR3 SNP rs3775296 was significantly associated with HTLV-1 infection and may be a protective factor against this viral infection.